Improving Community Financial Literacy to Prevent Illegal Online Lending and Investment Fraud - Afrizal Afrizal; Sipnarong Kanchanawongpaisan; Muhammad Hafiz Abd.Rashid; Phan Bao Giang; Syahriyal Syahriyal; Eka Nurlina; Stiven Jerry Immanuel Hutabarat (Eastasouth Institute, 2025)
The International Community Service program was implemented in Pematang Johar Village, Deli Serdang Regency, North Sumatra—an emerging semi-periurban area characterized by socioeconomic vulnerabilities that heighten residents’ exposure to illegal online lending and fraudulent investment schemes. Utilizing the Participatory Action Learning and Action Research (PALAR) approach, the program integrated experiential learning, critical reflection, group discussions, and locally relevant case studies to strengthen financial literacy. Evaluation results indicate substantial improvements across key indicators, including knowledge of licensed financial institutions, the ability to identify illegal financial practices, and overall financial prudence. These findings demonstrate that contextualized, community-based financial education effectively enhances risk awareness and encourages safer financial behaviour. The program further provides practical insights for designing scalable and replicable community financial literacy models applicable to similar semi-periurban contexts.